The Profile of Professional Identity of English Course Teachers in Yogyakarta - Maria Dewi Rosari (LET: Linguistics, Literature and English Teaching Journal, 2021)
The research horizon of teacher professional identity has been focusing a lot on formal education and emphasizing non-formal one less, although it plays an important role in fulfilling life-long education, as the Indonesian government has stated. Teacher candidates pursuing their bachelor study in English education also need to be equipped with in-depth insights on teacher interaction in English Course setting as they may also work in this non-formal education field as stated by the learning outcome goal of the association of Indonesian English Education major. This research aims to find out what profiles of professional identity English Course teachers in Yogyakarta had. An open-ended questionnaire elaborating the elements influencing teachers’ professional identity was distributed to 35 English Course teachers in Yogyakarta. The results show the English Course teachers possessed positive professional identity depicted by their high job satisfaction, occupational commitment, work motivation, and self-efficacy. Self-efficacy was founded as the strongest element and occupational commitment as the weakest element constructing the profile. Factors influencing the strength and the weakness of the elements of professional identity were elaborated to provide more thorough insight on how to provide working environment in which English Course teachers could work at their best and finally to retain them.